Photodegradation of new methylene blue N in aqueous solution using zinc oxide titanium dioxide as catalyst - Ali, Rusmidah; Ooi, Boon Siew (Penerbit UTM Press, 2006)
In this study, ZnO and TiO2 are used as photocatalyst to degrade the dye, New Methylene Blue N. The photodegradation rate was measured using UV-Visible spectrophotometer. New Methylene Blue N showed the absorption values at Î»=590 nm and Î»=286 nm. UV lamp (Î»=354 nm) is used in the photodegradation process. Results showed that ZnO is a better catalyst compared to TiO2. The degradation by ZnO showed TiO2 gave 81 % at Î»=590 nm and 77.75 % at Î»=286 nm. In contratst, the degradation for TiO2 was 25.68 % at Î»=590 nm and 26.37 % at Î»=286 nm. Percent degradation for New Methylene Blue N is 88.89 % and 68.94 % at Î»=590 nm and Î»=286 nm respectively when H2O2 was added. The mixture of ZnO and TiO2 in the ratio of 85: 15 (0.085 g: 0.015 g) is the most optimum mixture of photocatalyst with the degradation percentage of 96.97 % and 93.61 % at Î»=590 nm and Î»=286 nm. The addition of Cu2+ metal ion gave the highest percentage of degradation (83.83 % at Î»=590 nm) compared to other metal ions. The addition of Pb2+ gave the highest percentage of degradation at Î»= 286 nm with 81.25 %. The optimum condition was achieved at pH 5.90, which gave the highest percentage of degradation, 92.84 % and 89.30 % at Î»=590 nm and Î»=286 nm respectively.